(untitled) (Journal of actual problems of jurisprudence, 2018)
The legal status of women in traditional Kazakh society was more free and more secure than status of women in other countries of Central Asia. Kazakh women did not cover their face with a blanket, did not know seclusion, young men and women enjoyed freedom of communication. This had a significant impact on the educational process of the younger generation. In the Kazakh society there were no abandoned children, the property status of women was clearly regulated. Specificity of the traditional Kazakh law consisted in careful and attentive attitude to family ties, preserving the family property’s integrity, protecting of each member’s of society interests. In this regard, an important moment in the history of Kazakh customary law is the appearance of the code of laws «Zheti Zharғy», which included seven main chapters. The article deals with provisions regulating family-marriage and property relations, as well as provisions that establish punishment for crimes against women. Key words: Kazakhstan, woman, custom, law, punishment, crime, law, marriage, society, taboo.